Fabrication and evaluation of nanocontainers for lipophilic anticancer drug delivery in 3D in vitro model. Issue 4 (17th September 2020) - Borodina, Tatiana; Gileva, Anastasia; Akasov, Roman; Trushina, Daria; Burov, Sergey; Klyachko, Natalia; González‐Alfaro, Yorexis; Bukreeva, Tatiana; Markvicheva, Elena
Abstract: Presently, most of anticancer drugs are high toxic for normal cells and, and as a result, they have severe side effects. Moreover, most of the formulations are lipophilic and have poor selectivity. To overcome these limitations, various drug delivery systems could be proposed. The aim of the current study was to fabricate novel polysaccharide nanocontainers (NC) by one‐step ultrasonication technique and to evaluate their accumulation efficacy and cytotoxicity in 2D (monolayer culture) and 3D (tumor spheroids) in vitro models. NC with mean sizes in a range of 340–420 nm with the core‐shell structure are synthetized and characterized. The NC shell is composed from diethylaminoethyl dextran/xanthan gum polyelectrolyte complex, while the hydrophobic core was loaded with the lipophilic anticancer drug thymoquinone. To enhance NC accumulation in human breast adenocarcinoma MCF‐7 cells, the NC surface was modified with poly‐L‐lysine (PLL) or polyethylene glycol. Cell uptake of the NC loaded with Nile Red into the tumor cells was investigated by laser scanning confocal microscopy, fluorescent flow cytometry and fluorimetry. Modification of the NC with PLL allowed to obtain the optimal drug delivery system with maximal cytotoxicity, which was tested by MTT‐test. The developed NC are promising for lipophilic anticancer drug delivery.